Hubungan antara “Pemberitaan Pemerintahan” dengan Persepsi Politik Mahasiswa - Puspa Elissa Putri; Dedeh Fardiah (Bandung Conference Series: Journalism, 2021)
Abstract. Television has become the most influential mass media in Indonesia because of its ability to reach large numbers of audiences and deliver messages simultaneously. Through the mass media, they persuade through political messages conveyed to the public. For the public the media not only functions as an ordinary source of information, but also in the context of political momentum, both related to practical politics and those that are discourse or enlightenment, can be a reference for information. So researchers are interested in knowing whether the television mass media with the news is still biased to form the perception of the viewer. The research examines the relationship between government reporting on television, the Transmedia CNN Indonesia Bureau of West Java. The method used by researchers is quantitative research methods, with a correlational study approach. The researcher has the aim to find out whether there is a relationship between the reporting of the Transmedia CNN Indonesia Bureau of West Java related to infrastructure on student political perceptions, in the middle of the internet era. From the results of the study, there is a relationship between government reporting with indicators of prominence, and presenting news with political perceptions, with indicators of formation of perception, memory, and knowledge of politics. With agenda setting theory, and cultivation theory for perception, there is a relationship between government reporting on infrastructure, and the political perception of Pasundan University HI Department 2016 students. Abstrak. Televisi telah menjadi media massa yang paling berpengaruh besar di Indonesia karena kemampuannya menjangkau khalayak dalam jumlah yang banyak dan menyampaikan pesan secara serentak. Melalui media massa, mereka melakukan persuasi lewat pesan-pesan politik yang disampaikan kepada publik. Bagi publik media tidak hanya berfungsi sebagai sumber informasi biasa, tetapi juga dalam konteks momentum politik, baik terkait dengan politik praktis maupun yang bersifat wacana atau pencerahan, dapat menjadi rujukan informasi. Maka peneliti tertarik untuk mengetahui apakah media massa televisi dengan pemberitaanya masih bias membentuk persepsi yang menontonnya. Penelitian meneliti mengenai hubungan pemberitaan pemerintahan di dalam televisi yaitu Transmedia CNN Indonesia Biro Jawa Barat. Metode yang digunakan peneliti yaitu metode penelitian kuantitatif, dengan pendekatan studi korelasional. Peneliti memiliki tujuan yaitu untuk mengetahui apakah ada hubungan antara pemberitaan Transmedia CNN Indonesia Biro Jawa Barat terkait infrastruktur terhadap persepsi politik mahasiswa, ditengah era internet. Dari hasil penelitian tersebut, terdapat hubungan antara pemeberitaan pemerintahan dengan indikator penonjolan, dan penyajian berita dengan persepsi politi, dengan indikator pembentukan persepsi, daya ingat, dan pengetahuan tentang politik. Dengan teori agenda setting, dan teori kultivasi untuk persepsi, maka terdapat hubungan antara pemberitaan pemerintahan terkait infrastruktur, dengan persepsi politik mahasiswa Universitas Pasundan Jurusan HI angkatan 2016.